DISCLOSURE OF SUSTAINABILITY REPORTS ON ENERGY AND MINING COMPANIES: DOES OWNERSHIP STRUCTURE MATTER? - Husniyyah, Rifa; Kholid, Muamar Nur (Ultimaccounting Jurnal Ilmu Akuntansi, 2024)
Abstract” Companies operating in the energy and mining sectors significantly impact the communities and environment in their vicinity. Companies need to mitigate these adverse effects, and one way they can do this is by disclosing a sustainability report. Organizations use sustainability reports to communicate their commitment to sustainable business practices. This study examines the factors influencing sustainability report disclosure in companies within the energy and mining sectors between 2018 and 2021. This study implemented the multiplier linear regression data analysis procedure. The findings show that gender diversity in the board of directors, leverage, liquidity, and profitability do not significantly affect sustainability report disclosure. However, disclosure of sustainability reports is significantly impaired by the ownership structure. Keywords: Sustainability Report; Ownership Structure; Gender Diversity